Hemoglobin-to-red blood cell distribution width ratio in the relationship between occupational aluminum exposure and cognitive function impairment: a mediation analysis - Wang, Ruo-nan; Wang, Zhuo-hui; Hu, Wen-cheng; Kong, Fan-peng; Pei, Zi-yan; Song, Jing; Lu, Xiao-ting; Pan, Bao-long (Frontiers in Public Health, 2025)
ObjectiveTo investigate the partial mediating role of the inflammatory marker hemoglobin-to-red cell distribution width ratio (HRR) in the association between occupational aluminum exposure and cognitive function impairment, and its significance.MethodsIn this study, 401 workers from a Shanxi aluminum plant were selected by Cluster Sampling. Fasting elbow venous blood was collected for measuring routine blood counts, plasma aluminum concentration (P-Al) was measured using inductively coupled plasma mass spectrometry (ICP-MS), Montreal Cognitive Assessment (MoCA) was used to assess the cognitive function. Multiple linear regression was used to analyze the relationship between P-Al and cognitive function and HRR, and a restricted cubic spline model was used to fit the dose–response relationship, and mediated effects analysis was performed.ResultsThe median plasma aluminum concentration (P25,P75) of the workers was 50.74 (23.45, 85.52) μg/L, the mean HRR was 11.87, the median MoCA total score (P25,P75) was 24.00 (22.00, 26.00). A dose–response relationship showed that the MoCA score decreased with increasing P-Al. After adjusting for demographic and lifestyle covariates, multiple linear regression showed that P-Al was negatively correlated with the HRR and MoCA score. For each unit increase in P-Al, the HRR decreased by an average of 0.17, and the total MoCA score decreased by an average of 0.9. HRR mediated 9.89% of the effect between P-Al and MoCA score.ConclusionOccupational aluminum exposure negatively affects workers’ cognitive function and HRR levels. HRR can partially explain the effects of occupational aluminum exposure on workers’ cognitive function.